The role of cognitive individual differences in digital versus pen-and-paper writing - Vasylets, Olena; Mellado, M. Dolores; Plonsky, Luke (Studies in Second Language Learning and Teaching, 2022)
It is unknown whether and to what extent cognitive individual differences may play different roles in paper versus computer-based second language (L2) writing. This exploratory study is a first attempt to explore this issue, focusing on the effects of working memory and language aptitude on the quality of paper versus computer-based L2 writing performance. Forty-two Spanish learners of L2 English performed a problem-solving task either digitally or on paper, took a working memory n-back test, and completed LLAMA tests to measure language aptitude. The quality of their L2 written texts was assessed in terms of complexity, accuracy and fluency (CAF) measures. The results indicated that the role of cognitive individual differences may vary depending on the writing environment.